Analisis Faktor-Faktor Produksi Usahatani Kencur (Kaempferia galanga L.) Pada Lahan Gambut di Kecamatan Panai Hilir Kabupaten Labuhan Batu - Dalimunthe, Badrul Ainy; Siregar, Tumpal H.S.; Kardhinata, E. Harso (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This study aims to: (1) analyze the influence of inputriables, namely land area, labor costs, seed varieties, number of plants, and the cost of purchasing fertilizer on the yield of kencur on peatlands in Panai Hilir District Labuhanbatu Regency (2). Knowing the dominant variables that produce kencur results in Panai Hilir District, Labuhanbatu Regency. In order to find answers to the problems and objectives of the study then conducted a study of the factors that influence kencur production in Panai Hilir District, Labuhanbatu District by taking a sample of 75 samples consisting of farmers who worked for us, kencur while conducting research. Respondents who were given a questionnaire related to the production business carried out. The data obtained were analyzed with the help of SPSS program version 21.0. Research conducted, the variables used are seedling costs (X2), number of plants (X3), variable labor costs (X4) and fertilizer purchase variable (X5). From the research conducted obtained the results: (1) Addition of Seed Costs (X2) and Number of Planting (X3) can still increase the yield of kencur on peatlands. (2) Increasing the amount of Labor Costs (X4) and Fertilizer Costs (X5) will reduce the yield of kencur on peatlands. Variable Number of Plants (X3) is more dominant on the results of kencur production on peatlands than other variables in Panai Hilir District Labuhanbatu Regency